Tantangan yang Dihadapi Orang Tua serta Solusi dalam Mengasuh Anak Usia Dini di Era Digital - Pebrianti, Windi (TSAQOFAH, 2025)
The development of digital technology has brought significant changes to parenting patterns in early childhood. Children born as digital natives grow up with early exposure to digital devices, while many parents still experience a digital literacy gap that creates various challenges, such as gadget addiction, reduced social interaction, and the risk of exposure to age-inappropriate negative content. This study aims to examine the dynamics of digital parenting in early childhood, particularly regarding the opportunities and risks of digital technology use in the family context. The research employs a literature review method by analyzing various relevant journals, books, and reports that discuss early childhood parenting and the use of digital technology. The findings show that digital technology has two sides: positive impacts in the form of enhanced cognitive abilities, creativity, communication skills, and motor skills, as well as negative impacts in the form of disturbances to children’s physical, emotional, social, and moral well-being. Therefore, effective digital parenting requires active parental supervision, improved digital literacy, the implementation of rules governing gadget use, the selection of educational content, and a balanced proportion between digital activities and children’s real-world experiences in daily life.